(untitled) (Eurasian Research Bulletin, 2023)
There are quite a few options for the harmful effects of coronavirus infection on the liver. It is no secret that SARS-CoV-2 exploits angiotensin-converting enzyme 2 (ACE-2) as a receptor to enter the intracellular environment. It was found that ACE-2 is expressed to a greater extent on cholangiocytes , which makes the liver a possible target for the virus. A liver biopsy from SARS- CoV patients in 2002 showed a multiple increase in mitotic cells with eosinophilic bodies and balloon-like hepatocytes, suggesting that SARS- CoV may induce hepatocyte apoptosis and cause liver damage. Many studies have presented that SARS- CoV , through a specific protein 7a, can induce apoptosis at subcellular levels of various organs (including lungs, kidneys, and liver) in a caspase - dependent manner, proving the possibility that SARSCoV can directly act on hepatic tissue. First of all, at an early stage of SARS- CoV infection in patients, abnormal serum thresholds of cytokines and chemokines were found: serum levels of IL-1, IL-6 and IL-10 in patients with chronic diffuse liver diseases were higher than in patients with normal or slightly reduced liver function, calculating a tolerable correlation between liver damage and inflammatory reactions caused by coronovirus infection. In addition, SARS patients with HBV/HCV infection were more resistant to reversal of liver injury and severe hepatitis is usually associated with an increase in hepatitis virus replicatio n during SARS- CoV infection. Despite the fact that equal data on SARS-CoV-2 has not been achieved, chronic viral hepatitis probably does not increase the likelihood of a severe prognosis of COVID-19. CHB, which is more common in China than in Europe, does not appear to affect the outcome of COVID-19. Based on this, there is no credible argument to suggest that immunosuppression may even provide a kind of complex safety against immunopathological processes that contribute to lung damage in cases with more dangerous expressions of the disease. Most likely, this is due to the macrophage activation syndrome in pro-inflammatory syndrome, which qualifies as a cytokine storm and multiple organ failure. Systemic viral infections are partly associated with transient increases in transaminases, which may reflect generalized immune activation or inflammation caused by circulating cytokines without liver dysfunction, the so-called "bystander hepatitis" phenomenon - hepatitis not involved in the process. Liver damage with Covid -19 occurs in full due to hypoxia (oxygen depletion), which develops against the background of pulmonary insufficiency. Hypoxemia associated with severe pneumonia causes ischemic liver damage in patients with coronavirus infection. A decrease in the oxygen content in the body during hypoxic conditions can lead to the death of liver cells